PERKEMBANGAN LARVA IKAN KERAPU BEBEK (Cromileptes altivelis), SELAMA PROSES PENYERAPAN KUNING TELUR [Larval development of Humpback Grouper (Cromileptes altivelis), during absorption of yolk sac process] - Usman B; CR Saad; R Affandi; MS Kamarudin; AR Alimon (Jurnal Iktiologi Indonesia, 2003)
The newly hatched larva of humpback grouper, Cromileptes altivelis, had a yolk sac and an oil droplet. The average volume of the yolk sac was 0.15456 nm3, and the oil droplet was 0.00352 ^m3. The rates yolk sac and oil droplet absorption were very fast up to 33 hours after hatching (HAH), at which the remaining volumes of yolk sac and oil droplet were only 8.34% and 21.02% respectively. The yolk sac and oil droplet were totally absorbed when the larva reached 63 and 65 HAH. The average total length and height of the newly hatched humpback grouper larva are 1.865 mm and 0.460 mm respectively. At the completion of yolk sac absorption the average larval length and height increased to 2.54 mm, and 0.790 mm respectively. During this period, the development of its digestive system, eyes, mouth and pigments also occurred. The mouth opened before the yolk sac was totally depleted while the eye pigmen was not yet visible. AbstrakSuatu Kajian tentang perkembangan larva ikan kerapu bebek telah dilakukakn di laboraturium. Larva ikan kerapu bebek, Cromileptes altivelis, yang masih memiliki kuning telur dan butiran minyak digunakan sebagai hewan uji. Volume kuning telur dan butiran minyak masing-masing adalah 0,15456 ^m3 dan 0,00352 ^m3. Laju penyerapan kuning telur dan butiran minyak berlangsung sangat cepat mulai dari menetas sampai umur 33 jam setelah menetas, pada saat itu volume kuning telur dan butiran minyak hanya tinggal masing-masing sebesar 8,34% dan 21,02%. Kuning telur dan butiran minyak habis terserap pada saat larva berumur rata-rata 63 dan 65 jam setelah menetas. Rata-rata panjang dan tinggi larva ikan kerapu bebek yang baru menetas adalah 1,865 mm dan 0,460 mm. Panjang total dan tinggi larva rata-rata meningkat menjadi 2,54 mm dan 0,79 mm setelah kuning telur terserap habis. Selama periode tersebut, juga terjadi perkembangan saltiran peneernaan, mata, mulut dan pigmen. Mulut telah terbuka sebelum kuning telur habis terserap sedangkan pada saat tersebut pigmen mata masih belum tampak.